Meta-analysis of Physicochemical Characteristics in Beekeeping, Wild, and Stingless Bee Honey - Jordi Aditiya Prameswara; Tuti Suryati; Yuni Cahya Endrawati; Anuraga Jayanegara (Jurnal Ilmu Pertanian Indonesia, 2024)
The two most extensively beekeeping honeybee species were Apis mellifera and A. cerana. Other species that produced honey, albeit with infrequent cultivation, include A. dorsata, A. florea, and some stingless bees, including Trigona and Melipona. Different types of honeybees were known to affect the quality of honey. Hence, this investigation aimed to conduct a meta-analysis to examine the similarities in honey quality between honey sourced from beekeeping and wild honeybees. Data analysis was performed using the OpenMEE software, facilitating the calculation of effect size and standard error. The effect size and common error data were subsequently organized into separate columns within a CSV file. This CSV file was then imported into the JASP 0.16.2 software to conduct heterogeneity and Egger tests to detect potential publication bias. The findings indicated significant disparities in the quality of honey produced by beekeeping, wild, and stingless bee honey, as determined by various parameters, including pH value, moisture, total sugar, acidity, HMF (hydroxymethylfurfural), and diastase enzyme levels (p < 0.05). According to the results of the meta-analysis, honey from beekeeping exhibited superior quality to that of wild and stingless bees. However, the average values of all parameters still adhered to the established honey quality standards set by the Standar Nasional Indonesia and the International Honey Standard (IHS). Keywords: honey, honeybees, meta-analysis, physicochemical quality